Konsep Etika Belajar dalam Pemikiran Pendidikan Islam Klasik - Mulyasana, Dedi (Research and Development Institution, Darussalam Institute for Islamic Studies, 2019)
The concept of learning etics of Al-Zarnuji is an educational ethics reference which has widely employed in Islamic boarding school, Pesantren up to now. However, the concept has not been known and implemented yet in formal education. Exploring Al-Zarnuji's consept by using content analysis method, this study reveals some main findings regarding the learning ethics for learners. They are (1) advice of learning, (2) obligation of learning good and bad behavior, (3) prohibition of learning magic, (4) learning intention, (5) tawadlu, (6) the way of choosing teacher, (7) the way of choosing subject, and (8) the advice for learners.